The Role of Śaraṇāgati (Surrender to God) in Psychological Well-Being and Anxiety: A Correlational Study Among Bhakti Devotees (International Journal of Food and Nutritional Sciences, 2022)
The present study examined the role of Śaraṇāgati (surrender to God) in relation to psychological well-being and anxiety among Bhakti devotees. Rooted in Hindu spiritual traditions, Śaraṇāgati is considered a central tenet of Bhakti Yoga and involves ego renunciation, trust in divine will, and surrender of personal agency. A total of 40 adult participants (20 males and 20 females) who regularly engaged in devotional practices such as mantra chanting, scriptural study, and temple worship were surveyed using three standardized measures: a researcher-developed 20-item Śaraṇāgati Scale, the Generalized Anxiety Disorder-7 (GAD-7), and the 42-item Ryff Psychological Well-Being Scale. Correlational analyses revealed a significant positive relationship between Śaraṇāgati and psychological well-being (r = .92, p < .001) and a significant negative relationship with anxiety (r = –.78, p < .001). Regression analyses further confirmed that Śaraṇāgati was a strong predictor of well-being (β = 2.63, p < .001) and inversely predicted anxiety levels (β = –0.31, p < .001). Additionally, subscale-level analyses indicated that Self-Acceptance and Autonomy were the most positively influenced dimensions of well-being. These findings suggest that spiritual surrender may function as a protective psychological mechanism, enhancing emotional resilience and lowering anxiety among spiritually committed individuals. The study highlights the relevance of indigenous spiritual constructs such as Śaraṇāgati in understanding mental health within culturally embedded contexts.